PENGARUH KOMPETENSI GURU DALAM MENGAPLIKASIKAN CANVA TERHADAP MINAT BELAJAR SISWA PADA PELAJARAN AKIDAH AKHLAK DI MTs AL ISLAMIYAH JAKARTA BARAT - Purnamasari, Dewi; Zamroni, Moh (Jurnal Tarbiyah Jamiat Kheir, 2025)
This study aims to analyse the effect of teacher competence in applying Canva on student learning interest in Akidah Akhlak lessons in class VII at MTs Al Islamiyah Jakarta Barat. Based on initial observations, conventional teaching methods without technology-based media have resulted in low student learning interest. Using a quantitative correlational design, data were collected from 20 respondents (selected via simple random sampling from 55 students) through a Likert-scale questionnaire (30 statements), observation, interviews, and documentation. Data analysis employed descriptive statistics, Pearson Product Moment correlation, t-test, and coefficient of determination. The results indicate a significant influence between teacher competence in applying Canva and student learning interest, with a correlation coefficient of 0.460 (sufficient category). Teacher competence contributes 21.16% to learning interest, while 78.84% is influenced by other factors. Student responses were highly positive: 83.46% for teacher competence and 94.17% for learning interest, with 7 indicators reaching 100%. Observations revealed significant behavioural changes when learning shifted to Canva—students became more enthusiastic, actively participated in quizzes, and classroom absences decreased. Gender differences were also found: female students showed unimodal learning interests and greater adaptability, while male students demonstrated multimodal interests requiring more varied stimuli. The findings align with Wina Sanjaya's learning innovation theory, Edgar Dale's Cone of Experience, and Jejen Musfah's pedagogical technology competence theory. Conclusions demonstrate that Canva application significantly transforms static learning into engaging, interactive instruction. Practical implications include enhancing teachers' pedagogical technology competence through continuous training and adequate facility provision to accommodate diverse student characteristics.